Analysis of Household Food Security Policy: Case of Food Security Village Programme, Indonesia - Rusliyadi, Muhamad; Jamil , Azaharaini Bin Hj Mohd; Kumalasari , Ratna Tri (Asian Journal of Agriculture and Rural Development, 2019)
The study analyses a food self-sufficiency village programme (DMP programme) at household level in the Central Java province of Indonesia. The data of the DMP programme was collected through unstructured and semi-structured questionnaires and focus-group discussions. The survey was conducted in four villages, each consisting of 100 samples based on a purposive and clustered sampling technique. The study compares the implication between indicators before and after the policy. It was found that the impact of the DMP programme on the villages was positive. The level of poverty in each village has been significantly reduced by 8-40% after the introduction of the programme. The composite food security analysis at the household level shows the positive impacts of the programme.